2015
DOI: 10.1016/j.jalz.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hippocampal atrophy and neuropathology markers: A 7T MRI validation study of the EADC‐ADNI Harmonized Hippocampal Segmentation Protocol

Abstract: Objective The pathologic validation of European Alzheimer's Disease Consortium Alzheimer's Disease Neuroimaging Center Harmonized Hippocampal Segmentation Protocol (HarP). Methods Temporal lobes of nine Alzheimer's disease (AD) and seven cognitively normal subjects were scanned post-mortem at 7 Tesla. Hippocampal volumes were obtained with HarP. Six-micrometer-thick hippocampal slices were stained for amyloid beta (Aβ), tau, and cresyl violet. Hippocampal subfields were manually traced. Neuronal counts, Aβ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 54 publications
3
51
0
Order By: Relevance
“…Traditionally, hippocampal volumetry considers the hippocampus as a single anatomical entity and, thus, only provides a global volumetric measure. However, the hippocampal formation is an anatomically complex structure that is composed of multiple subfields . This multilateral structure is classically composed of the hippocampal CA1, CA2, and CA3 subfields, the dentate gyrus (DG), and the subiculum .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, hippocampal volumetry considers the hippocampus as a single anatomical entity and, thus, only provides a global volumetric measure. However, the hippocampal formation is an anatomically complex structure that is composed of multiple subfields . This multilateral structure is classically composed of the hippocampal CA1, CA2, and CA3 subfields, the dentate gyrus (DG), and the subiculum .…”
mentioning
confidence: 99%
“…However, the hippocampal formation is an anatomically complex structure that is composed of multiple subfields. 11 This multilateral structure is classically composed of the hippocampal CA1, CA2, and CA3 subfields, the dentate gyrus (DG), and the subiculum. 12 As different cellular and molecular characteristics in hippocampal subfields, 13 these subfields are regarded as differentially vulnerable to processes associated with stress and conditions like depression.…”
mentioning
confidence: 99%
“…The field of manual tractography segmentation is decades behind fields such as gray nuclei or hippocampi manual segmentation on this matter. The latter has been refining segmentation protocols for the past decade and has already reached the state harmonized segmentation protocol and was evaluated with reproducibility in various settings (Apostolova et al, ; Boccardi et al, , ; Frisoni et al, ; Wisse et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given the association between tau deposition and atrophy in the whole hippocampus or hippocampal subfields (Apostolova et al, ), hippocampal subfield atrophy might be contributed by hippocampal tau deposition, which coincides with neocortex Aβ accumulation in early stage (Braak, Alafuzoff, Arzberger, Kretzschmar, & Del Tredici, ). Supporting preliminary evidence from ADNI MCI group suggested that Aβ‐associated progressive hippocampal subfield atrophy was more pronounced in MCI with p‐tau positivity, but not in MCI with p‐tau negativity (Table Se‐14).…”
Section: Discussionmentioning
confidence: 99%
“…However, similar results were observed between datasets. Secondly, other variables may also contribute to hippocampal subfield atrophy and disease progression (e.g., tau pathology and cerebrovascular factors) in addition to Aβ (Apostolova et al, ; den Heijer et al, ). Future studies need to take into consideration the spatial quantification of Aβ instead of an average Aβ burden, and determine the contributing variables and the temporal relationships underlying disease progression.…”
Section: Discussionmentioning
confidence: 99%